Development of a measure for maternal confidence in knowledge and understanding and examination of psychosocial influences at the time of a child's heart surgery - Tallon, M.; Kendall, Garth; Snider, P. (Blackwell Publishing Ltd, 2015)
Purpose: The purpose was to develop a maternal confidence in knowledge and understanding scale (Maternal Knowledge and Understanding Scale [MKUS]) and examine the effect of psychosocial factors at the time of a child's heart surgery. Design and Methods: Using cross-sectional design, the MKUS was developed and tested. Validated instruments were used to examine the impact of psychosocial factors. Results: The MKUS showed acceptable internal consistency (Cronbach's alpha .78). Higher levels of maternal anxiety and lower levels of social support were associated with lower MKUS scores (p < .05). Practice Implications: A measure of maternal confidence in knowledge and understanding could draw attention to psychosocial factors and opportunities to enhance nursing support.